Gender in Religious Ethics and Practices - Columbus, Ogbujah (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2017)
There is a somewhat symbiotic relationship between religion and culture: religious practices shape, and are shaped by the culture within which they thrive. When people in a given culture adopt a specifc religion,their culture begins to assimilate only the ethos and practices that are acceptable within that religion; and when a particular religion arises within a given culture, its ethics and rituals are usually grounded on the tenets of that culture. Thus, having strong roots in patriarchal and androcentric cultures, Abrahamic religions cannot shy away from the encumbrances of ﬂawed gender relationships. With the help of feminist studies, we have unearthed the insidious force of gender in the assignment of roles ‘skewed’ to favour men over women not only in politics and commerce but also in religious and social lives. The idea is not to take a knock at the spiritual values represented by these bodies, but to highlight the underlying inﬂuence of gender on the various ethics and practices of Judaism, Christianity and Islam.